Antioxidant and antimicrobial performance of different Argentinean green tea varieties as affected by whey proteins - Von Staszewski, Mariana (2011)
Green tea contains a high percentage of polyphenols, which are potent antioxidant and antimicrobial agents. However, interactions between polyphenols and food components may decrease their potential benefits. The aim of the study was to evaluate whether the antioxidant and antimicrobial capacities of different Argentinean green tea varieties could be affected by whey proteins. The results showed some degree of masking in the antioxidant and antimicrobial activity of green tea infusions when whey proteins are present. The degree of inhibition of antioxidant activity in each variety did not depend on the polyphenol concentration, indicating the importance of the particular polyphenol composition of each variety. The CH 410 variety exhibited the best performance as antioxidant and antimicrobial, even in the presence of whey proteins. The antimicrobial effects in the presence of whey proteins correlated with the polyphenol content of the green tea infusions and increased with the reduction of whey protein concentration. The antimicrobial effectiveness was similar within a pH range from 4.0 to 7.0, allowing its application to a wide group of foods.